2017
DOI: 10.1128/jcm.00191-17
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiological and Molecular Characterization of an Invasive Group A Streptococcus emm 32.2 Outbreak

Abstract: An emm32.2 invasive group A streptococcus (iGAS) outbreak occurred in Liverpool from January 2010 to September 2012. This genotype had not previously been identified in Liverpool, but was responsible for 32% (14/44) of all iGAS cases reported during this time period. We performed a case-case comparison of emm32.2 iGAS cases with non-emm32.2 control iGAS cases identified in the Liverpool population over the same time period to assess patient risk factors for emm32.2 iGAS infection. The emm32.2 iGAS cases were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Recent reports have described GAS outbreaks affecting homeless populations that were caused by strains of emm types 82, 83, 87, 101, and 114 in Canada [7], 44 in France [34], and 32 and 66 in Great Britain [35, 36]. One common theme between the current emm74 and prior emm59 epidemics, as well as in these other reports, is that the offending GAS strains belong to emm types of pattern D (skin tropism) or E (generalist, ie, both throat and skin tropism) [37, 38].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have described GAS outbreaks affecting homeless populations that were caused by strains of emm types 82, 83, 87, 101, and 114 in Canada [7], 44 in France [34], and 32 and 66 in Great Britain [35, 36]. One common theme between the current emm74 and prior emm59 epidemics, as well as in these other reports, is that the offending GAS strains belong to emm types of pattern D (skin tropism) or E (generalist, ie, both throat and skin tropism) [37, 38].…”
Section: Discussionmentioning
confidence: 99%
“…Outbreaks of GAS disease have previously been linked to the acquisition of mobile genetic elements, such as an ongoing polyclonal emm12 and emm1 scarlet fever outbreak in Hong Kong and mainland China associated with horizontal acquisition of multidrug resistance and a superantigen-encoding prophage (6). Outbreaks of invasive GAS disease have also been associated with acquisition of, or mutations within, genotypic regulatory systems that result in increased phenotypic virulence (20,21). However, this clonal invasive GAS outbreak differs from previously reported outbreaks (6,20,21) because it was linked primarily to the acquisition of a transposable element with no obvious virulence determinant.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that isolate 112327 is an outbreak strain with characteristics that suggest it is hypervirulent, e.g. it has 19 extra genes, five of which are associated with an increase in virulence 39 . We have shown in this current study that isolate 112327 is more virulent in an invasive bacteraemia model and produced significantly more SLO which is likely to be one of the causes of its increased capacity to cause host death.…”
Section: Discussionmentioning
confidence: 99%
“…As previously published in Cornick et al , between January 2010 to September 2012, the Respiratory and Vaccine Preventable Bacteria Reference Unit (RVPBRU) in the United Kingdom confirmed a total of 14 cases of emm type 32.2 invasive GAS in the Merseyside area. Over the same time period, 30 non- emm type 32.2 invasive GAS infections were collected alongside 20 non-invasive pharyngitis GAS isolates supplied by the Royal Liverpool University Hospitals Trust and Alder Hey Children’s Hospital 30 . The Merseyside outbreak emm type 32.2 isolates (n = 14) were selected for this study alongside a selection of non- emm type 32.2 isolates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation